تقييم استراتيجيات إدارة سلاسل التجهيز في المنظمات الصناعية الواقع و الطموح : دراسة استطلاعية في الشركة العامة لصناعة الادوية و المستلزمات الطبية-نينوى - Dr. Amer Ismail Hadid (PROSPECTIVE RESEARCHES, 2023)
The research presents an evaluation of supply chain management strategies in the Iraqi industrial sector, which represents one of the most important pillars in the building and developing the economy of the state. The public company for the pharmaceutical industry and medical supplies/ Nineveh is chosen as sample. Data collected involves workers of both high and low Positions, in senior management represented by managers, heads of departments and units and production units, which are responsible for the activities of management of the supply chain. (30) Questionnaire forms were distributed. A combination of statistical methods included (duplicates, percentages, the mathematical community, and standard deviations, as well as coefficients of variation) were used in data analysis. Based on the results of the analysis, the research comes up with a set of conclusions; the most important is that the company surveyed has adopted a mix of strategies for managing the supply chain in their work, with different reliability levels. This researcher presented a set of recommendations as the need to give greater freedom for the company surveyed to work autonomy with regard to procurement without reference to the policies imposed on them by the Ministry of Industry and Minerals.